Cyberbullying Victimization in WhatsApp Classmate Groups among Israeli Elementary, Middle, and High School Students - Aizenkot, Dana (Journal of interpersonal violence, 2021)
In recent years children and adolescents lead their social lives in the virtual world no less than in the real one. Social networking sites such as WhatsApp play a major role as popular social communication platforms. More than 97% of Israeli youth use WhatsApp and are members of WhatsApp classmate groups. The growing use of WhatsApp is accompanied by increased frequency of cyberbullying, that is, intended and repeated aggressive online behavior aimed to inflict harm. Cyberbullying victimization has received a fair amount of attention due to its association with serious psychosocial, affective, behavioral, and academic problems. Although much has been written about cyberbullying on Facebook, literature about WhatsApp and cyberbullying is scarce. Based on a large-scale survey that examined the prevalence and expressions of cyberbullying the current cross-sectional study provides a detailed description of cyberbullying victimization in WhatsApp classmate groups across grade level and gender among Israeli school-age children and adolescents. The study included 4,477 elementary, middle, and high school students in Israel who completed questionnaires regarding cyberbullying victimization in their WhatsApp classmate groups. According to the study findings, approximately 30% of all survey participants report personal victimization from cyberbullying in their WhatsApp classmate groups, and almost double that report victimized aggression at least once in the recent past. Demographic variables such as school grade level and gender appear to moderate cyberbullying. Increased cyberbullying was found in elementary school compared with middle and high school, and more female compared with male students were victims of cyberbullying in WhatsApp classmate groups. The article outlines several areas of concern in cyberbullying research and discusses issues that future research might address. Education policy guidelines and implications for intervention are also discussed.